GnRH-antagonist programming versus GnRH agonist protocol: a randomized trial. (February 2015) - Hershko Klement, Anat; Berkovitz, Arie; Wiser, Amir; Gonen, Ofer; Amichay, Keren; Cohen, Ilan; Ghetler, Yehudith; Shulman, Adrian
Abstract: Objective: Testing the ability to program IVF GnRH-antagonist cycles to avoid weekend oocyte retrieval. Study design: Preliminary randomized clinical trial. Patients presenting an indication for IVF or IVF-ICSI were assigned into either the Treatment Group – GnRH antagonist protocol, programmed to start stimulatory agents on a Friday, with oral 2 mg estradiol valerate twice a day from the 2nd day of cycle until the first Friday to follow, or to the Control Group – long luteal GnRH agonist protocol. Results: The performance of 27 Treatment Group patients and 24 Control Group patients was analyzed. Cycle dynamics were not clinically or statistically different except for a significant difference in the number of follicles measuring ≥18 mm on hCG administration day. There were no differences in the number of aspirated ova, fertilization rates, embryo quality or number of embryos to be transferred. Pregnancy rate was 41.7% in the Treatment Group and 50% in the Control Group ( P > 0.5). Only one patient assigned to the Treatment Group had a weekend retrieval. Conclusions: Preliminary results demonstrate no compromise related to follicular estrogen programming in a GnRH antagonist protocol and provide reassurance regarding the ability to achieve programming goals.